RETRACTED: Legal Analysis Of Electronic Information Dissemination That Violates Moral Norms - Grace Geovanni (Fakultas Hukum Dehasen, 2023)
RETRACTION NOTICE Following up on the review of articles published in Jurnal Hukum Sehasen carefully, thoroughly, and considering the article entitled